Immigration detention : law, history, politics - Wilsher, Daniel, 1966- (Cambridge : Cambridge University Press, 2012)
'The liberal legal ideal of protection of the individual against administrative detention without trial is embodied in the habeas corpus tradition. However, the use of detention to control immigration has gone from a wartime exception to normal practice, thus calling into question modern states' adherence to the rule of law. Daniel Wilsher traces how modern states have come to use long-term detention of immigrants without judicial control. He examines the wider emerging international human rights challenge presented by detention based upon protecting'national sovereignty' in an age of global migration. He explores the vulnerable political status of immigrants and shows how attempts to close liberal societies can create'unwanted persons' who are denied fundamental rights. To conclude, he proposes a set of standards to ensure that efforts to control migration, including the use of detention, conform to principles of law and uphold basic rights regardless of immigration status'--
Introduction and overview : free movement of persons and liberty of the person -- The creation of immigration detention : from free movement to regulated borders in America and the United Kingdom -- Modern immigration detention and the rise of the permanent bureaucratic enterprise -- International law and immigration detention : between territorial sovereignty and emerging human rights norms -- Negotiating detention within the European Union : redefining friends and enemies -- Security and immigration detention : the problem of internment in peacetime -- Global migration and the politics of immigration detention -- Restoring the rule of law and influencing politics : placing boundaries around detention.
Includes bibliographical references (p. 355-375) and index.
Keywords: Illegal aliens; Alien detention centers; Refugees -- Legal status, laws, etc